Bacteriological Quality, Antimicrobial Activity, and Public Health Implications of Selected Herbal Remedies Sold in Offa, Kwara State, Nigeria - Usman, Kolawole Muftau (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2025)
The increasing use of locally produced herbal concoctions in Nigeria for medicinal purposes has raised concerns about their safety, as many are used without scientific validation. This study aims to investigate the bacteriological quality and histo-pathological effects of select herbal concoctions to assess their safety to human use. Thus, bacteriological quality of herbal remedies, the identity of isolates and histopathological effects of select herbal remedies using Wistar albino were determined using standard methods. Findings from means bacterial population of bacterial isolates of herbal remedies ranged between 5.0 and10.0 (x106 cfu/ml), and no significant difference recorded among the values obtained at p≤0.05. Bacterial genera isolated from the herbal remedies included Proteus mirabilis, Bacillus subtilis, Pseudomonas sp., Streptococcus sp. and Enterococcus sp. The minimum inhibitory concentrations (MICs) of herbal remedies ranged between 60 and 90 (mg/ml) concentrations. Findings from toxicological studies confirmed that herbal remedies had adverse effects on the intestine, liver and kidney of the test Wister albino rats. This study suggests that extra care should be taken before and while taking herbal remedies despite its proven potency in curing some human ailments.